Limnandi Evangeli and Hlangani Bafundi : An exploration of the interrelationships between Christian choruses and South African songs of the struggle - Tönsing, J. Gertrud (HTS teologiese studies, 2017)
This article explores the interrelationships between Christian choruses and South African songs of the struggle, which sometimes used the same tunes. The development of each genre is explained and the interrelationship between them analysed. One example is studied in more detail. Songs deeply influence people, be it in their faith or in their political action. A critical awareness of how these songs functioned and continue to function can deepen our understanding of the South African struggle for freedom as well as enriching our praxis today.